IMPLIKASI PENERAPAN APLIKASI SISTEM INFORMASI MANAJEMEN KINERJA DAN GOOD GOVERNMENT TERHADAP KINERJA ORGANISASI - Setia Budi, M. Arief (JSI: Jurnal Saudagar Indonesia, 2024)
This study aims to determine the effect of the implementation of the performance management information system application and good government on the performance of the Banda Aceh Culture and Tourism Office. The population in this study were all employees. The sample collection technique in this study was a census, so that the number of respondents was 191 people. Data were collected by distributing questionnaires online which were linked to a google form. The Likert scale was used to measure data in the field and analyzed using multiple linear regression. The test results concluded that the partial implementation of SIMANJA had an effect on organizational performance. This also applies to the role of the good government variable on the dependent variable. Simultaneously, the results of the F test prove that the implementation of the performance management information system application and good government on the performance of the Banda Aceh culture and tourism office